Resource annotation framework in a georeferenced and geospatial digital library - Lim, Ee Peng (2009)
In this paper, we present a resource annotation framework for georeferenced and geospatial digital libraries and discuss its application in G-Portal. The framework is flexible for managing annotations of heterogeneous web resources. It allows